The suitability of Ni-Co catalysts in the dry reforming reaction - Mtetwa, Bongani Leslie (Department of Chemical Engineering, 2022)
In recent times, the dry reforming of methane has received significant interest as an alternative process through which synthesis gas can be produced. This is because dry reforming combines methane and carbon dioxide which are both greenhouse gases into synthesis gas which is used in the production of synthetic fuels and chemicals. The main problem faced by the dry reforming reaction is the formation carbon which causes catalyst deactivation. Noble metal catalysts such as ruthenium and rhodium have shown great promise as dry reforming catalysts because of their resistance to carbon formation, but they are expensive making their use on an industrial scale unlikely. This has led to nonnoble metals such as nickel and cobalt being considered as potential catalysts. Bimetallic nickel-cobalt (Ni-Co) catalysts have garnered a lot of interest as dry reforming catalysts as combining these two metals is believed to produce catalysts that would be more stable than monometallic nickel and cobalt catalysts. The objectives of the project were to investigate the suitability of nickel-cobalt (Ni-Co) alloy catalysts with different compositions as well as monometallic nickel and cobalt catalysts as dry reforming catalysts. In doing so, special emphasis was placed on understanding the effect of the Ni-Co ratio on catalyst activity, stability, and deactivation mechanisms. In the study, seven catalysts with varying Ni-Co ratios were prepared. The catalysts had a 10 wt.% active metal (nickel and cobalt combined) loading and were supported on magnesium aluminate (MgAl2O4). Catalyst testing was carried out on all the catalysts at 700 °C for a period of 12 hours to compare their performance in the dry reforming reaction. The results from catalyst testing showed that the Ni-Co catalysts that were nickel rich (70% and 90% nickel in terms of active metal) were the most active catalysts. This was because these catalysts achieved higher methane and carbon dioxide conversions in comparison to the rest of the catalysts. The most surprising result from catalyst testing was that the monometallic nickel catalyst showed very limited activity and was unstable. Post run catalyst characterisation using Raman spectroscopy showed that the Ni-Co composition of the catalysts influenced the type of carbon deposited on the catalysts during catalyst testing. This was because the carbon deposits on the cobalt rich Ni-Co catalysts were found to be more graphitic in nature compared to those on the nickel rich Ni-Co catalysts. However, the Ni-Co composition of the catalysts was found to have no influence on the amount of carbon deposited on the catalysts based on the results obtained from TGA analysis. In addition, post run catalyst characterisation showed that there was carbon formation on all the catalysts studied except for the monometallic nickel catalyst. This showed that there is a need to investigate additional means through which the carbon formation can be limited during catalyst testing. The co-feeding of water in the dry reforming of methane is one such measure that should be investigated.